The Influence of Role Conflict and Role Ambiguity on Employee Job Satisfaction of Transportation Companies in Indonesia - Wirson Bongga; Ade Irma Susanty (International Journal of Supply Chain Management, 2018)
Transportation companies in Indonesia are businesses prioritizing services to the community. Job satisfaction of the employees is the major driving factor in improving the services. This study analyzes the influences of role conflict and role ambiguity on employee job satisfaction of transportation companies in Indonesia with the total samples of 154 people. The data is analyzed using path analysis. The result of this study has obtained coefficient of determination (CD) or R square (R2), in which the overall R square (R2) value for the role conflict and role ambiguity is 62.8%. Role conflict and role ambiguity have significant negative impact, both simultaneously and partially on employee job satisfaction. Therefore, in order to improve the employee job satisfaction, transportion companies in Indonesia need to decrease the rate of role conflict and role ambiguity. The transportation companies in Indonesia are suggested to build a good communication environment, maximize the evaluation system of work and improve office facilities in order to spur employee morale and increase employee loyalty to the companies.